Uncovering land tenure insecurities: tips for tenure responsive land-use planning in Ethiopia. Issue 3 (3rd April 2019) - Chigbu, Uchendu; Alemayehu, Zebad; Dachaga, Walter
ABSTRACT: Land-use planning, although a mechanism for development, can also generate insecurity during its implementation. This article argues that tenure security and land-use planning should not be implemented in isolation from each other. It posits that land-use planning – rather than restricting the security of people's tenure – has the potential to serve as a means of securing tenure. The article explores tenure (in)security elements in land-use planning as a crucial challenge in the urban town of Gelan Sidama Awash, Ethiopia. Using data collected through stakeholders' interviews, it uncovers their tenure security challenges, and outlines a set of measures for enhancing tenure security through land-use planning.